The Influence of Motivation, Responsibility, Courage and Lecturer Teaching Performance on Student Satisfaction in Higher Educatiom - . Wahyu; . Fatimah; . Sarbaini (Emerging Science Journal, 2023)
Students have always been looking for the best colleges or universities to continue their studies. These prospective students will try to find references by having one of them seek information from students who are currently at or have studied at the intended college or university. One of the factors they asked about was learning satisfaction at the intended college or university. Student learning satisfaction depends on several variables: student motivation, student responsibility, student courage in learning, and the lecturer’s teaching performance. Based on this, the present research aimed to examine the four variables that have influence on student learning satisfaction, individually and in a group. The research used a quantitative approach and was conducted on students and lecturers at the Universitas Lambung Mangkurat, one of the state universities in Banjarmasin, South Kalimantan Province in Indonesia. The sample consisted of 83 participants, was studied using a descriptive correlational research model, and was drawn using a simple random sampling technique. Data were obtained through questionnaires and document studies and then analyzed using a regression model using IBM SPSS Statistics 20.0. The findings revealed that student motivation, student responsibility, student courage in learning, and lecturer teaching performance positively and substantially affected student learning satisfaction at the Faculty of Teacher Training and Education of Universitas Lambung Mangkurat, either partially or simultaneously. Doi: 10.28991/ESJ-2023-SIED2-04 Full Text: PDF